2017
DOI: 10.1111/jpc.13467
|View full text |Cite
|
Sign up to set email alerts
|

Personal smartphones for neonatal diagnostic imaging: A prospective crossover study

Abstract: Diagnosis of neonatal pneumothorax was as accurate using a smartphone as viewing CXR images displayed on a computer screen when clinicians were presented with X-rays with diagnosis of pneumothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Nonetheless, mobile consultations are becoming more and more common in assisting clinical decision‐making 20 . Also, studies show that a digital photo of a CXR on a mobile phone is not inferior to standard modalities 21,22 . In addition, there was no difference in mobile use or screen resolution between study groups (Table 1).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nonetheless, mobile consultations are becoming more and more common in assisting clinical decision‐making 20 . Also, studies show that a digital photo of a CXR on a mobile phone is not inferior to standard modalities 21,22 . In addition, there was no difference in mobile use or screen resolution between study groups (Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…show that a digital photo of a CXR on a mobile phone is not inferior to standard modalities. 21,22 In addition, there was no difference in mobile use or screen resolution between study groups (Table 1).…”
Section: Limitationsmentioning
confidence: 95%
“…To the best of our knowledge, the clarity and interpretability of chest radiographs transferred via smartphone have not yet been comprehensively validated. We were only able to find one study that addressed this issue in the field of neonatology, but it was limited to the diagnosis of pneumothorax .…”
Section: Discussionmentioning
confidence: 99%
“…However, smartphones and web applications have not yet been recommended for interpreting chest radiographs. A study of the online diagnosis of neonatal pneumothorax showed that neonatal clinicians could interpret chest radiographs viewed on a smartphone or on a computer screen with equal accuracy .…”
Section: Introductionmentioning
confidence: 99%
“…However, there can be different resolutions due to differences in digital imaging software and hardware, hence, producing different qualities of digital X-ray films. 8 These variations open an opportunity to explore image enhancement techniques on images of digitized X-ray films. [9][10][11][12][13][14][15] In this paper, we investigate the use of CLAHE image processing techniques as a proof of concept and we validate the output via quantitative metrics and qualitative evaluation by a medical practitioner.…”
Section: Introductionmentioning
confidence: 99%